EFEKTIFITAS TERAPI MUROTTAL QUR’AN TERHADAP PERUBAHAN KADAR SITOKIN IL-6 PADA PASIEN TUBERKULOSIS PARU - zakariyati, zakariyati; Burhanuddin, Burhanuddin; Saleh, Ariyanti (Journal of Islamic Nursing, 2017)
This research aimed to nvestigate whether the Murottal Qur’an therapy was effective in changing the IL-6 levels inpatients with lung tuberculosis. The research subjects were  the lung tuberculosis patients who underwent the OAT therapy at intensive phase (≤2 month). The total subjects of 20 people were devided in  to 2 groups: Group I (control group, group II (receiving the Murottal Qur’an therapy. The measurement were conducted two times that is on 0 day and 15th.. The research was conducted at the health center of Minasa Upa and Pelamonia Second class Hospital.The research results indicated that by using the wilcoxon test indicated that the OAT therapy, OAT therapy  and Murottal Qur’an Therapy showed the same effectiveness on the change of levels with the value of p>0,005, but the picture of the change dynamics of IL-6 levels was better presented by the OAT therapy and Murottal Qur’an.